2009
DOI: 10.1623/hysj.54.6.1007
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the effects of levee heightening on flood propagation: example of the River Po, Italy

Abstract: The effects of human activities on flood propagation, during the period 1878-2005, in a 190-km reach of the middle-lower portion of the River Po (Northern Italy) are investigated. A series of topographical, hydrological and inundation data were collected for the 1878 River Po geometry and the June 1879 flood event, characterised by an inundated area of 432 km 2 . The aim of the study is two-fold: (1) to show the applicability of flood inundation models in reconstructing historical inundation events, and (2) to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
104
0
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(107 citation statements)
references
References 19 publications
1
104
0
2
Order By: Relevance
“…Even though the mutual interactions between different types of factors are not well understood, they are still important. The research on interactions between sociological and hydrological processes has been proposed by Di Baldassarre et al (2009) with the River Po (Italy) used as a case study. Di Baldassarre et al (2013) presented a simplified model describing the relationship between socio-economic development and the hydrology of a river basin.…”
Section: The Challenges Of Flood Adaptation Strategymentioning
confidence: 99%
“…Even though the mutual interactions between different types of factors are not well understood, they are still important. The research on interactions between sociological and hydrological processes has been proposed by Di Baldassarre et al (2009) with the River Po (Italy) used as a case study. Di Baldassarre et al (2013) presented a simplified model describing the relationship between socio-economic development and the hydrology of a river basin.…”
Section: The Challenges Of Flood Adaptation Strategymentioning
confidence: 99%
“…One of the advantages of TELEMAC-2-D as finite elements model is the possibility to use structured or non-structured computational meshes. These last, in particular, provide a densification of the triangular elements at certain critical points and allow to better describe the topographical discontinuity that influences the inundation process, such as levees, road and railway embankments (Domeneghetti, 2014;Di Baldassarre et al, 2009b). For this preliminary study, we refer to a non-structured triangular mesh densified at the major discontinuities that can influence our process of flooding, such as boundaries, channels, roads and railways.…”
Section: -D Numerical Modelmentioning
confidence: 99%
“…what is usually identified as "residual flood risk"; see e.g. Castellarin et al, 2011;Di Baldassarre et al, 2009b) it would lead to higher damages, than those which would occur if rivers could expand freely in the surrounding plain. This paradox is called "levee effect" and describes the frequent phenomenon in which the flood control systems encourages urbanization in areas that are even closer to rivers (Tobin, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Increases in flood stage for constant discharge conditions over the past few decades have been noted for the Mississippi River (Criss and Shock 2001, Pinter et al 2001, 2008, Jemberie et al 2008) and most of the researches attributed this phenomenon largely to river management practices such as levee construction and extensive channelization. Di Baldassarre et al (2009) reported a strong relationship between the length of the levee system in the Po River basin, Italy, and a corresponding increase in water depth for major flood events in the last century. Possible causes of this relationship include a significant reduction in the width of the floodplain open to the passage of flood flows and an enhanced backwater effect that slows the water down, resulting in the increase of water depth (Heine and Pinter 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the placement, increasing the height of levees without proper investigation often causes more damage. Numerical modelling suggests that increasing the height of levees may enable local flood control, but often results in higher discharge downstream leading to levee failure with disastrous consequences (Di Baldassarre et al 2009). Hydraulic models in conjunction with economic considerations have been applied to investigate the role of levee heights in flood mitigation, but in a deterministic manner (Julien et al 2010, Meunier andMerwade 2014).…”
Section: Introductionmentioning
confidence: 99%